Gamification on Cryptocurrencies to Increase Public Investment Interest - Sakmar, Moeng; Surya, Rizky Andhika; Hartinah, Siti (PT.KARYA GEMAH RIPAH, 2025)
The development of cryptocurrencies continues to experience a very rapid in-crease with the prediction of average growth of more than 1 million investors every month around the world. However, it is different in Indonesia, people do not know widely what cryptocurrency is and how to invest in cryptocurrency. The Indonesian Ministry of Trade noted that in the second quarter (Q2) of 2020, cryptocurrency investors experienced an increase of up to 6.4 million investors, but when compared to the total population of Indonesia, this figure is still very far below 1%, plus economic conditions after the Coronavirus pandemic are getting worse. discourage people from investing. When viewed from the fundamental side, cryptocurrency assets can be said to be quite strong against the pandemic, compared to the stock market and mutual funds listed on the Indonesian stock exchange (IDX) which have decreased due to the coronavirus pandemic. In this study, we propose a gamification method by focusing on the introduction of cryptocurrency investments with the aim that people in Indonesia can be more familiar with and invest in cryptocurrency, the methods, and systems that we propose will at the same time reward users in the form of crypto assets to attract people to better understand the opportunities. investing in cryptocurrency.